THE ROLE OF NATURE PROTECTION ACTIVITIES IN THE FORMATION ENVIRONMENTAL COMPETENCE OF YOUNGER SCHOOL STUDENTS - Ломака, О.С. (Modern engineering and innovative technologies, 2024)
The article defines the peculiarities of environmental competence in the formation of the consciousness of younger schoolchildren. The analysis of scientific works makes it possible to generalize views on the formation of environmental consciousness. Educ